2006
DOI: 10.1073/pnas.0605921103
|View full text |Cite
|
Sign up to set email alerts
|

Pinoresinol: A lignol of plant origin serving for defense in a caterpillar

Abstract: Pinoresinol, a lignan of wide distribution in plants, is found to occur as a minor component in the defensive secretion produced by glandular hairs of caterpillars of the cabbage butterfly, Pieris rapae. The compound or a derivative is appropriated by the larva from its normal food plant (the cabbage, Brassica oleracea). Pinoresinol was shown to be absent from the secretion if the larva was given a cabbage-free diet but present in the effluent if that diet was supplemented with pinoresinol. Pinoresinol is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 25 publications
2
52
0
1
Order By: Relevance
“…Lignin and other phenolics can strengthen cell walls and therefore can be anti-nutritional (BrodeurCampbell et al, 2006;Schroeder et al, 2006). Some phenolics and sesquiterpenes along with other volatiles can repel herbivores from oviposition on host plants (Henzell & Hall, 1974;DeMoraes et al, 2001;Huber et al, 2006).…”
Section: Plant Secondary Metabolitesmentioning
confidence: 99%
“…Lignin and other phenolics can strengthen cell walls and therefore can be anti-nutritional (BrodeurCampbell et al, 2006;Schroeder et al, 2006). Some phenolics and sesquiterpenes along with other volatiles can repel herbivores from oviposition on host plants (Henzell & Hall, 1974;DeMoraes et al, 2001;Huber et al, 2006).…”
Section: Plant Secondary Metabolitesmentioning
confidence: 99%
“…Caterpillars of P. rapae do take up pinoresinol from B. oleracea plants to excrete them from their glandular hairs: whether it is present in the fat body as well is unknown (Schroeder et al 2006). A different study showed P. brassica caterpillars take up flavonoids (Ferreres et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It also receives increasing interest in the field of plant-host interactions (Allwood et al 2006(Allwood et al , 2008Choi et al 2004Choi et al , 2006. In both the aforementioned studies into the uptake of pinoresinol and of flavonoids by Pieris caterpillars a broad-spectrum metabolomics-type analysis was essential to discover the compounds (Ferreres et al 2007;Schroeder et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…4CL, p-coumarate:CoA ligase; C3H, p-coumarate 3-hydroxylase; CA, caffeic acid; CAD, cinnamyl alcohol dehydrogenase; CCR, cinnamoyl-CoA reductase; CSE, caffeoyl shikimate esterase; F5H, ferulate 5-hydroxylase; Fer-CoA, feruloyl-CoA; HCT, p-hydroxycinnamoyl-CoA:quinate/shikimate p-hydroxycinnamoyl transferase; PAL, phenylalanine ammonia-lyase; pCA, p-coumaric acid; POX, peroxidase; LAC, laccase. of these coupling products is not well understood, but they have been postulated to serve as antioxidants (Kitts et al, 1999) or to play a role in plant defense (Harmatha and Nawrot, 2002;Hano et al, 2006;Schroeder et al, 2006). In contrast to the free-radical lignin polymerization, the monolignol cross-coupling toward (neo)lignans is guided by dirigent proteins (Davin et al, 1997) that have a "dirigent domain" that acts as a scaffold that orients two monolignol radicals during dimerization, leading to the formation of a specific stereoisomer.…”
Section: Introductionmentioning
confidence: 99%